Safety assessment of a three‐dimensional‐printed autologous omentum patch: An application on the kidneys as a new treatment approach - Hyunwoo Jo; Janghwan Kim; Jin‐Wook Kim; Boyun Kim; Bo Young Choi; Kyuyong Kang; Jina Ryu; Min Su Kim (Wiley, 2023)
Abstract Recently, the field of regenerative medicine has made great strides in the development of new treatments for various organ dysfunctions. One of the most promising new approaches is the use of three‐dimensional (3D) printing and autologous tissues. In this study, we evaluated the safety of a 3D‐printed autologous omentum patch to kidneys using large animals. A total of seven micropigs underwent transplantation of the 3D‐printed autologous omentum patch. Twelve weeks after transplantation, the safety was evaluated by measuring body weight, blood, and the renal resistive index. In addition, biopsy samples were histologically analyzed. The results showed no surgical complications, renal functional hematological changes, or inflammatory responses. Therefore, this study provides important insights into direct therapy to kidneys with a 3D‐printed patch made of autologous tissue. Furthermore, it has the potential for the development of new therapies for various organ dysfunction.